Problem-based learning in orthogonal projection drawing: A quasi-experimental study on vocational machining students’ technical drawing achievement - Aprilia Eka Salwa; Syahril Syahril; Eko Indrawan; Gulzhaina K. Kassymova (Jurnal Pendidikan Teknologi Kejuruan, 2026)
This study examined the implementation of Problem-Based Learning (PBL) and its effect on Grade X Machining Engineering students’ cognitive achievement in Technical Drawing, particularly orthogonal projection. The study used a quantitative quasi-experimental design with a non-equivalent control group. The participants were 70 students at SMK Negeri 5 Padang, divided into an experimental class taught using PBL and a control class taught using conventional instruction. Data were collected through pretest and post-test scores using a validated multiple-choice test on orthogonal projection. The final instrument consisted of 28 valid items with a KR-20 reliability coefficient of 0.914. Descriptive statistics, Shapiro-Wilk normality tests, Levene’s homogeneity test, and an independent samples t-test were used for data analysis. The results showed that both groups improved after instruction, but the experimental class achieved a higher increase. The mean score of the experimental class rose from 53.57 to 79.28, while the control class increased from 53.67 to 64.29. The t-test showed a significant post-test difference between groups, t (68) = -10.152, p < 0.001. These findings indicate that PBL supports stronger cognitive achievement in orthogonal projection learning by engaging students in investigation, discussion, presentation, and evaluation. The findings directly recommend PBL for visual technical topics in vocational classrooms.